IMPROVING THE MECHANISMS FOR DEVELOPING EFFECTIVE MANAGEMENT STRATEGIES IN HIGHER EDUCATION - Levakov Izzatulla Nematillaevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article examines the features of improving the mechanisms for the development of effective management strategies in higher education. Approaches to the evaluation of the quality of higher education are based on the results expected by the subjects interested in the educational process. A scientific conclusion and practical recommendations related to the economic evaluation of the quality of higher education are given.